Standarisasi Mutu Tanaman Herbal Aur-Aur (Commelina longifolia L.) dan Tanaman Bungango (Flueggea virosa Royle) - A. Mu’thi Andy Suryadi; Muhammad Taupik; Ariani. H Hutuba; Andi Makkulawu; Mahdalena Sy. Pakaya (State University of Gorontalo, 2022)
In the developing materials for traditional medicines, it is necessary to standardize the quality of plant materials. Tuhus, quality, stability, and safety. This study aims to determine several standardization parameters and determine the flavonoid content of the 70% ethanol fraction of aur-aur leaves (Commelina longifolia L.) and bungango leaves (Flueggea virosa Royle) to ensure that the fractions have quality and measurable parameter values. The fraction was standardized with two parameters, thus specific and non-specific, and flavonoid content test using UV-Vis spectrophotometry method. The results of phytochemical screening, the fraction containing flavonoid compounds is 70% ethanol fraction. Standardization of specific parameters showed the organoleptic results of both aur-aur (Commelina longifolia L.) and bungango (Flueggea virosa Royle) leaf fractions in the form of a semi-solid viscous fraction, black in color, and characteristic odor. The content of water soluble extract and ethanol soluble extract of aur-aur (Commelina longifolia L.) leaf fraction were 22.84%, ethanol soluble extract 25.03%, while the fraction of Bungango (Flueggea virosa Royle) leaf was 30.70%. and 27.31%. Standardization of non-specific parameters showed the results of water content 21.40%, total ash content 8.92%, acid insoluble ash content 0.043%, drying shrinkage 10.48%. The results of non-specific standardization of bungango leaves (Flueggea virosa Royle) showed a moisture content of 14.45%, a total ash content of 9.62%, an acid insoluble ash content of 1.31%, a drying shrinkage of 10.64%. The results for the analysis of the flavonoid content of the 70% ethanol fraction of aur-aur leaves and bungango leaves were carried out at a wavelength of 438.36 nm. The total flavonoid content was calculated by the standard linear equation of quercetin, namely y= 0.0648x + (-0.0232) with a correlation coefficient (r2) = 0.9948 with the total flavonoid content of aur-aur leaf and bungango leaf each of 3.57. % and 9.578%.